Estrategia didáctica "SEMANTIC TRAINING" para la producción de textos escritos-en inglés, en estudiantes del segundo grado de educación secundaria, de la Institución Educativa "Juan Jiménez Pimentel" del distrito de Tarapoto, en el año 2008 - Trigoso Terleira, Carol Gianina (2009)
Teaching and learning process of the English language in Peruvian high schools does not have the appropriate methodology, the means and the motivation which may guarantee understanding and comprehension of the significant and meaning of the linguistic signs. This problem gets worse when teachers only choose very wide texts and inadequate to the real situation and context of the students. This leads to lack of interest for reading. In the other hand very difficult terminology does not allow students to understand the reading so they just ask someone to translate the texts. So, our aim is to contribute to solve this problem. The objective of our investigation is to demonstrate that the didactic strategy "Semantic training" will help to improve the students' skills at writing in English. The mentioned strategy was developed in JUAN JIMENEZ PIMENTEL, SECONDARY SCHOOL, SECOND GRADE HIGH SCHOOL, Tarapoto, PERÚ, South America, during de second trimester, 2008. Our hypothesis is as follows: if we apply the "Semantic training" strategy, then students' skills at writing in English will improve, (second grade students of JUAN JIMENEZ PIMENTEL High School, Tarapoto city, PERÚ, South America). In order to demonstrate our hypothesis, we developed an applied type investigation, that is to say an experimental research, with a quasi-experimental design, having a pre-test and a post-test, with a control group. Sixty-eight students, from the second grade of secondary school, of the JUAN JIMENEZ PIMENTEL High School, Tarapoto city, PERÚ, South America, in 2008, were the sample, which was divided in two groups: 34 students were the "experimental group", and 34 students were the "control group". Both groups had a test before and after the experiment. The data analysis of the post-test of the experimental and the control groups, using normal distribution in "z", allowed us to demonstrate the hypothesis. The evidence is that Zc equals 6, 17 which is higher than Zt which equals 1,64; so Zc is located in the rejection area. So, if we develop the "Semantic training " strategy, then second grade high school students, will improve their skills at writing in English, in JUAN JIMENEZ PIMENTEL High School, Tarapoto city, PERÚ, South America).